CHARACTERIZATION AND MOLECULAR DOCKING OF CINNAMIC ACID DERIVATIVES: POTENTIAL INHIBITORS OF CYCLOOXYGENASE ENZYMES - BUNU, SAMUEL J; ALFRED-UGBENBO, DEGHINMOTEI; MIEDIEGHA, OYEINTONBARA; BABA, HARUNA (Innovare Journal of Life Sciences, 2023)
Objective: The pathology of every disease passes through the inflammation stage; hence, the design and optimization of potential lead compounds as anti-inflammatory agents is still a significant part of medicinal chemistry globally. Methods: In this study, we designed, synthesized, and characterized some cinnamic acid derivatives and performed molecular docking of the derivatives on the human cyclooxygenase-1 (COX-1) enzyme. Results: The elemental analysis showed the presence of different functional groups. Molecular docking was performed on the active sites of COX-1 (PDB ID: 6Y3C). The derivatives as well as the standard compound, were observed to interact mainly with the arginine residue of the target protein. The dioxomethylene substituted derivative showed the highest binding affinity, compared with other derivatives, including the standard drug (−6.8 kcal/mol). Conclusion: The binding affinity observed in the cinnamic derivatives, and biological activities correlations revealed that compounds with the dioxomethylene group would be good anti-inflammatory lead molecules, as they demonstrated high affinity to the target protein and biological activities. Thus, these compounds can serve as potential lead compounds for the design, and development of effective anti-inflammatory agents, targeted to inhibit the human COX-1 enzyme involved in biological inflammatory mechanisms.